Connectives as both Semantic and Pragmatic Links in Children’s Narratives - Peterson, Carole (Linguistica Atlantica, 1989)
Children’s (3 to 9 years old) use of the connectives so, because, and but during conversational narration was assessed. The function of each of these connectives for pragmatic versus semantic purposes was studied, and it was found that all are used to fulfill both roles. Specifically, the following pragmatic functions were revealed: (a) to mark the beginning of a narrative or component episode, (b) to change the focus from event recapitulation to listener-directed contextual remarks and vice versa, (c) to indicate that strict temporal succession is violated, and (d) to mark a narrative conclusion. Children show competence in using connectives pragmatically to regulate narrator-listener interaction and to move among the different levels of discourse that are found in conversational narration.